Calculation of Parametric Vibrations of Homogeneous in Thickness Visco-Elastic Bar in Visco-Elastic Soil - I.T. Pirmamedov (Механика машин, механизмов и материалов, 2009)
In the present paper we consider parametric vibrations of rectilinear inhomogeneous in thickness bar allovering for physical and geometrical non-linearity, buried under visco-elastic soil. The problem is solved by variational method typical curves for dependence of applied force on frequency are constructed.